The Ultimate Recycling? Positing the Effect of Past Life Belief on Fair Trade Consumption: A Preliminary Study - Musa, Shireen (Journal of Scientific Exploration, 2023)
As societal and environmental injustices are increasingly prevalent, expectations for organizations to implement sustainable practices, such as Fair Trade, have grown. Previous research has demonstrated that Fair Trade consumers have the emotional attribute of compassion and the educational trait of desire for sustainability awareness. This paper builds on prior research by introducing consumers’ spiritual attributes of past life belief (PLB) and positing the effect of PLB on Fair Trade consumption (FTC). The article is novel as it is the first to introduce and link the spiritual attribute of PLB to FTC while addressing racism, religious discrimination, sexism, classism, societal and environmental stewardship, and nationalism. The sample size for this study is one hundred fourteen, N=114. Results were analyzed through hierarchical multiple regression. It was found that PLB is positively related to FTC.